PPT1 is a negative regulator of STING signaling in cancer cells and its inhibition reactivates immune surveillance in cold tumors - Shreya R. Chowdhury; Chaitanya N. Parikh; Arshia N. Kaur; Kelly D. DeMarco; Hadiya K. Giwa; Alok K. Mishra; Katherine C. Murphy; Lin Zhou; Boyang Ma; Tianyi Ye; Junhui Li; Haibo Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
Immunotherapy modalities have revolutionized cancer treatment for a number of metastatic and treatment-refractory tumor types. Still, many malignancies that lack T cell infiltration and are termed immunologically “cold” fail to respond to these modalities. One approach to increase tumor immunogenicity has been to induce stimulator of interferon gene (STING) and downstream interferon signaling that is often dysregulated in cold tumors. Despite some early success of STING agonists in preclinical cancer models, these approaches have not been successful in the clinic due to poor tumor penetrance and systemic toxicities. Here, we performed a genome-wide CRISPR screen to uncover therapeutic targets to activate STING expression in human tumors. We identified the lysosomal hydrolase Palmitoyl Protein Thioesterase1 (PPT1) as a negative regulator of STING highly expressed in cold ovarian and prostate tumors. Genetic or pharmacological PPT1 suppression increased STING protein stability and its downstream activation of interferon and inflammatory cytokine signaling to enhance T cell migration. Treatment of preclinical prostate and ovarian cancer models expressing low levels of STING with the small molecule PPT1 inhibitor GNS561 enhanced STING expression and activation, leading to infiltration and activation of cytotoxic T cells that turned these tumors “hot” and reduced tumor growth, fibrosis, and dissemination without toxicity. Further analysis demonstrated that PPT1 is associated with reduced STING expression, CD8 + T cell numbers, overall survival, and immunotherapy outcomes in ovarian and prostate cancer patients. Thus, PPT1 inhibition may be a promising approach to activate STING and potentiate the effects of immunotherapy in cold tumors.